The Laureate English Program: Taking a research informed approach to blended learning - Debra Marsh; Christopher Johnson (Laureate Education Inc, 2013)
The aim of this case study is to describe the implementation of the Laureate English Program (LEP), the consequent decision to roll out blended learning across the network, and the Laureate-Cambridge University Press research partnership. Phase 1 of the research was completed in September 2012. The goal of this first phase was to gain a general understanding of student profile, computer literacy and competence, student levels of achievement, and student feedback on their blended learning experience. Six hundred and forty-eight students and 35 teachers responded to a questionnaire, which included multiple choice questions and open ended questions requiring extended comment. The questionnaires revealed that less than 25% of the Laureate student group had ever learned a language online before, which impacted significantly on student perception and use of online learning content. Furthermore, the first phase of research has revealed the impact that a complex interplay of different factors has on the relative effectiveness of these blended programs, and it has acknowledged that research is central to informed decision making in order to provide for effective blended learning. DOI: 10.18870/hlrc.v3i1.103